Music Therapy for the Rehabilitation of Dyslexic Children - Chen, Hui Meng; Yoesbar, Djaelani (IJISRT, 2020)
Dyslexia is a learning disorder. A dyslexic has difficulties in reading, writing, spelling, and counting skills. They also encounter problems in recognizing the sound of letters. In Malaysia, there are several approaches used to help dyslexics with certain skills - these are multisensory as well as: auditory exercises using a computer, intervention programs, and rehabilitation programs. Multisensory and multimedia methods were more often used in conducting intervention programs for dyslexics in Malaysia. It is therefore the aim of this study to apply music therapy to help children with dyslexia using experimental research in the form of singing treatment. The purpose of this research was to test the effectiveness of singing treatment in improving the reading and writing skills of dyslexic children. Apart from that, this research also aims to improve the reading and writing skills of dyslexic children through singing treatment. This research was conducted at the Learning and Resources Centre of Dyslexia Association of Sarawak. Mixed method and One-Group Pretest-Posttest designswere applied to collected data. Four dyslexic children were selected to receive this treatment. They were named Subjects A, B, C, and D. Furthermore, they were divided into two groups:- Subjects A and B have a basic phonics ability and so were grouped together, whereas; Subjects C and D were grouped togetheras they do not have a basic phonics ability. The resultsshow that this treatment was effective in improving the reading and writing skills of Subjects C and D. The t-value for this group is 1.40, which this value is below the significance level, 2.74. Besides that, this treatment was less effective in improving the reading and writing skills of Subjects A and B. The t-value for this group is 6.05, exceeding the significance level, 2.74.